Argo [videorecording (DVD)] - Affleck, Ben, 1972-; Arkin, Alan; Goodman, John, 1952-; Donovan, Tate; Garber, Victor; Cranston, Bryan, 1956-; Desplat, Alexandre; Mendez, Antonio J.; Bearman, Joshuah (Warner Home Video, 2013)
On November 4, 1979, Iranian militants stormed the American embassy in Tehran and captured dozens of American hostages, sparking a 444-day ordeal. There's a little-known footnote to the crisis: six Americans escaped and a mid level agent named Antonio Mendez devised an ingenious yet incredibly risky plan to rescue them.